1977
DOI: 10.1128/iai.15.3.789-795.1977
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive transfer of immunity from mice immunized with ribosomes or live yeast cells of Histoplasma capsulatum

Abstract: This investigation was designed to compare the role of lymphoid cells and immune serum in protective immunity induced by immunization with ribosomes or live yeast cells of Histoplasma capsulatum. Spleen cells, peritoneal cells, and serum from CH mice immunized with Histoplasma ribosomes or live cells were transferred intravenously to separate groups of syngeneic recipients. All recipients along with a set of immunized and control mice were challenged intravenously with 4 x 106 yeast cells of H. capsulatum, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

1979
1979
2010
2010

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 17 publications
(22 reference statements)
1
13
1
Order By: Relevance
“…It is generally held that a critical host defense mechanism activated in response to infection by Histoplasma capsulatum is the so-called cellmediated immune response. Support for this concept is provided by several experimental studies: first, by the demonstration that lymphocytes from mice immunized by sublethal infection with H. capsulatum can mediate suppression of intracellular growth of the fungus in normal mouse macrophages (17); second, by demonstration of increased susceptibility to Histoplasma infection in congenitally athymic mice (38) or in conventional mice after treatment with antilymphocyte serum and cytotoxic agents (1,8,12); and third, by evidence for transfer of adoptive immunity against Histoplasma by spleen or peritoneal cells from immunized donors (36).…”
mentioning
confidence: 99%
“…It is generally held that a critical host defense mechanism activated in response to infection by Histoplasma capsulatum is the so-called cellmediated immune response. Support for this concept is provided by several experimental studies: first, by the demonstration that lymphocytes from mice immunized by sublethal infection with H. capsulatum can mediate suppression of intracellular growth of the fungus in normal mouse macrophages (17); second, by demonstration of increased susceptibility to Histoplasma infection in congenitally athymic mice (38) or in conventional mice after treatment with antilymphocyte serum and cytotoxic agents (1,8,12); and third, by evidence for transfer of adoptive immunity against Histoplasma by spleen or peritoneal cells from immunized donors (36).…”
mentioning
confidence: 99%
“…There is a strong clinical association between AIDS and invasive histoplasmosis (62), cryptococcosis (63) and coccidiodomycosis (64,65), suggesting that cell-mediated immunity is critical. The importance of cell-mediated immunity has been demonstrated further by studies where the transfer of immune lymphocytes to naive syngeneic recipients has afforded protection against histoplasmosis (66), blastomycosis (67) and coccidiodomycosis (68). It has been demonstrated that both CD4 and CD8 cells participate in host defence to cryptococcus (56,69) and histoplasma (70).…”
Section: Recruited Mechanisms Of Host Defencementioning
confidence: 99%
“…Cell-mediated immune responses are of primary importance in protective immunity to histoplasmosis and in diseases caused by other facultative intracellular parasites. In histoplasmosis the evidence for this concept is provided by several studies: first, lymphocytes from mice immunized by sublethal infection with Histoplasma capsulatum can mediate suppression of growth of the fungus within normal macrophages (7,8); second, the higher susceptibility of congenitally athymic mice (24) or normal mice following treatment with antilymphocyte serum and cytotoxic agents (1,6); and third, the adopive transfer of anti-Histoplasma immunity by spleen and peritoneal cells from immunized donors (9, 19,21,25).…”
Section: Introductionmentioning
confidence: 99%
“…capsulatum (19). The immunity is transferable to syngeneic recipients by immune lymphoid cells but not with immune serum (19,21). The immune spleen and peritoneal cells which confer immunity to histoplasmosis are Tlymphocytes and their active proliferation in recipients is necessary for the expression of anti-Histoplasma immunity.…”
Section: Introductionmentioning
confidence: 99%